THE CORRELATION BETWEEN INSTRUCTIONAL LEADERSHIP AND EFFICACY AMONG THE CAMBODIAN PUBLIC LOWER SECONDARY SCHOOL TEACHERS - Sopheng Tep (Asosiasi Dosen Perguruan Tinggi Islam, 2022)
Researchers have explored instructional leadership's correlation with teacher efficacy in developed countries, yet there is no research to broadly study in developing country contexts, especially in the public schools of Cambodia. Hence, the research objective is to find a significant correlation between the instructional leader and the efficacy of Cambodian public lower secondary school teachers. The researcher uses a quantitative method to collect data through a survey questionnaire. Also, the researcher uses the Pearson Correlation coefficient, a tool in SPSS version 23, to find the correlation between the instructional leader and teacher efficacy. There were 100 participants who were public lower secondary school teachers who participated in the data collection process. The key finding points out that the instructional leader has a high positive correlation with teacher efficacy, which is statistically significant. Thus, the instructional leader certainly correlates with efficacy among Cambodian public lower secondary school teachers. The result is significant for instructional leaders and relevant stakeholders in improving teachers' efficacy to fulfill their tasks better than before. Besides, future studies should focus on similar topics with different theories and a larger sample size at other institutions across the country. Finally, future studies should also emphasize qualitative and mixed-method designs.